HOUSING AFFORDABILITY PREFERENCES FOR ‘RUMAH SELANGORKU’ SCHEME - Afiqah, Nurul; Kamarul Bahrin, Nur Erisha Syahiera; Rozman, Ahmad Tajjudin (Journal of Sustainable Technology and Applied Science (JSTAS), 2020)
Housing is described as one of the most universal concerns for a country's welfare that reflects people's perception of living standards. Every homebuyer must have their own natural preferences in buying a house. Apart from that, this study focused on housing affordability preferences for “Rumah Selangorku” Program. This research aims to rank the house buyers’ preferences elements for ‘Rumah Selangorku’ in specifically De Kiara Apartment, Shah Alam, Malaysia. This research also identifies the preferences elements for house buyers from the literature. The questionnaire survey has been distributed towards respondents which are the occupants of De Kiara Apartment, Shah Alam. Thus, the results indicated price at the first ranked followed by locality; design; space standard; and facilities and services.